ANALYSIS OF ELEMENTARY SCHOOL STUDENTS’ REASONING PROCESS IN UNDERSTANDING THE PHENOMENON OF FALLING FRUIT: MISCONCEPTION OR P-PRIMS? - Juliyanto, Eko (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This research aims to unveil elementary schools’ reasoning process in understanding the phenomenon of falling fruit with their limited knowledge about it. This research employed qualitative approach with the approach of The Investigation of Lived Experience assisted with Cognitive Psychology. The data of this research were obtained by written test and interview. The subjects of this research were the students of 4th and 6th grade with the samples of 3 students in each class. The result showed that the reasoning of elementary school students were mostly inductive. Only one respondent had deductive reasoning. The result also showed that the case of p-prims with inductive analysis was caused by analogy and intuition, while p-prims with deductive analysis happened due to inadequate ability to explain certain phenomenon. Misconception was formed by two inductive reasonings, (1) inductive reasoning with unrelated premises and (2) inductive reasoning with related premises; however, incorrect preposition. Other findings related to this research is the initial understanding of the respondents was formed as p-prims and some other was formed as misconception.